Hydrocarbon deposition and soil microflora as affected by highway traffic - Tuhácková, J; Cajthaml, T; Novák, K; Novotný, C; Mertelík, J; Sasek, V (Environmental pollution (Barking, Essex, 2001)
The proximity of a busy highway (90,000 vehicles/day) increased the amount of polycyclic aromatic hydrocarbons (PAHs) in soil at the depth of 5-15 cm from 106 ng/g as a grassland background to 3095 ng/g dry soil at the highway verge (a sum of 10 PAH species). The PAH concentration was related to the distance from the source and exhibited a biphasic character, which is interpreted in terms of bimodal distribution of the exhaust microparticles with different rates of deposition. Similarly, the tendency of benz(a)anthracene, chrysene, benzo(b)fluoranthene, benzo(k)fluoranthene, and indeno(1,2,3-cd)pyrene to decrease their proportion with distance from the highway, in contrast to phenanthrene, fluoranthene, pyrene, benzo(a)pyrene, and benzo(g,h,i)perylene, was attributed to their prevalent localisation on the heavier particle fraction. The abundance of bacteria (8.33 x background) and fungi (3.17 x background) close to the highway is thought to be a consequence of hydrocarbon deposition from the traffic that serves as a significant energetic input into the soil. The elevated concentrations of hydrocarbon substrates, as indicated by PAHs, increased both the absolute and relative numbers of the microbial degraders of diesel fuel, biphenyl, naphthalene, and pyrene. Their maximum numbers at 0.5-1.5 m from the pavement reached 1.3 x 10(4), 1.2 x 10(5), 1.1 x 10(4), and 6.6 x 10(3) colony-forming units (CFU) or infection units per gramme dry soil, respectively. On the other hand, the number of anthracene degraders (1.1 x 10(3) CFU per g dry soil) remained close to the detection limit of the enumeration technique used (0.1-0.2 x 10(3) per g dry soil), consistently with the absence of anthracene and higher linear PAHs in the investigated soil samples. The amounts of persisting PAHs justify artificial inoculation with effective degrader strains in the vicinity of motorways.
Keywords: polycyklické aromatické uhlovodíky; Soil Pollutants; populační dynamika; látky znečišťující půdu; Environmental Exposure; výfukové emise vozidel; vystavení vlivu životního prostředí; Motor Vehicles; Polycyclic Aromatic Hydrocarbons; Population Dynamics; motorová vozidla; Vehicle Emissions; půdní mikrobiologie; Soil Microbiology